Considerazioni sui culti ittiti connessi al ciclo lunare - Francesco G. Barsacchi (Asia Anteriore Antica)
The Hittite sources document the existence of two different religious ceremonies connected to the lunar cycle, both defined as EZEN4 ITUKAM, “festival of the month”. The first one is performed either at the beginning of the month or at full moon, and it is often attested in the cult inventory texts as part of the cult due to local deities. In addition to these regular ceremonies, which should more correctly be indicated as “monthly festivals”, a “festival of the month” is performed by the Hittite king at the beginning of every month in order to sacralyze a time perceived as particularly meaningful. In this official ceremony, whose fragments are currently filed under CTH 591, several originally autonomous rites directed to the moon in particular lunar phases were included. This paper, besides providing a general overview of the Hittite religious ceremonies connected to the moon cycle, briefly analyzes some of these rituals, trying to determine their potential relationship to CTH 591.